Workaholism – psychological and social determinants of work addiction - Soroka, Ewelina; Iwanicka, Aleksandra; Olajossy, Marcin (Current Problems of Psychiatry, 2020)
Introduction. Workaholism as a psychological and social phenomenon is the object of only a few empirical studies. Despite the fact that the phenomenon of addiction to work was not specified in the ICD-10 or DSM-5 Classifications, the authors of this paper have decided that it is worth considering its preconditions.Materials and method. Based on the review of the available literature, the topic of work addiction was discussed and the main determinants of workaholism and the so-called workaholic personality were presented.Results. The paper presents the author’s theoretical proposition of workaholism notion which postulates the existence of a form of addiction to work, which has its source in personality and motivation.Conclusions. Undoubtedly, workaholism is addictive, but only obsessive-compulsive components may not be sufficient to determine its nature. Workaholism adopts a three-dimensional structure including behavioral, cognitive and affective aspects. Further research on this issue is needed.